2018
DOI: 10.1021/acssuschemeng.8b04011
|View full text |Cite
|
Sign up to set email alerts
|

Improving Ni(OH)2/C Supercapacitive Performances through Mixed Solvents and Thermal Treatment of XC-72

Abstract: A Ni(OH) 2 /XC-72 nanocomposite was first synthesized via a solvothermal method in mixed solvents of ethylene glycol and H 2 O; using a smaller amount of ethylene glycol not only reduces the cost but also enhances the electrochemical performances of the composite. X-ray diffraction patterns indicate that α-Ni(OH) 2 and β-Ni(OH) 2 are coexistent in the Ni(OH) 2 /XC-72 composite. The capacitance of α,β-Ni(OH) 2 /XC-72 increases from 1649.3 F g −1 of α-Ni(OH) 2 /XC-72 and 1232.5 F g −1 of β-Ni(OH) 2 /XC-72 to 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…2, the crystal structure of the as-synthesized PtNi/C was further explored by X-ray diffraction (XRD). The diffraction peak between 20 • and 30 • is consistent with the Vulcan XC-72 [30] (Figure S2). Compared with the standard Pt, all of the characteristic peaks shift to a higher angle due to the Pt lattice contraction after alloying with Ni.…”
Section: Characterization Of Ptni/c Nanostructuressupporting
confidence: 71%
“…2, the crystal structure of the as-synthesized PtNi/C was further explored by X-ray diffraction (XRD). The diffraction peak between 20 • and 30 • is consistent with the Vulcan XC-72 [30] (Figure S2). Compared with the standard Pt, all of the characteristic peaks shift to a higher angle due to the Pt lattice contraction after alloying with Ni.…”
Section: Characterization Of Ptni/c Nanostructuressupporting
confidence: 71%
“…However, more detail observation through DSC curve demonstrates the presence of two close endothermic peaks which are centered at 185 and 215 °C the, which could be related to the decomposition of α and β-Ni(OH) 2 to NiO, respectively. The result is in good compromise with references [17][18][19][20]30].…”
Section: Structural and Morphological Characterizationsmentioning
confidence: 71%
“…Al-, Co-, Mn-, Zn-, Y-and Cu-substituted α-Ni(OH) 2 [15][16][17]. Furthermore, some studies have been performed on the coprecipitation of mixed α/β-Ni(OH) 2 [18][19][20]. For example, Wang et al found that α/β-Ni(OH) 2 has better electrochemical performance than Al-substituted α-Ni(OH) 2 and usual β-Ni(OH) 2 [21], and they also observed that α/β-Ni(OH) 2 has better supercapacitive characteristics than β-Ni(OH) 2 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 2a, the typical diffraction peaks at 12.3°, 33.3°, 38.7°and 61.3°of 2θ are indexed to (003), (101), (015) and (113) diffraction peaks of α-Ni(OH) 2 (JCPDS 38-0715) [45]. The characteristic peak located at 23.6°is assigned to rGO, demonstrating the successful reduction of GO.…”
Section: Syntheses and Characterizations Of Rgo-ni(oh) 2 Compositesmentioning
confidence: 87%